Accelerating the Development of Higher-Level Clinical Thinking in Novice Nurses. Issue 5 (September 2017) - Flanders, Sonya A.; Gunn, Sharon; Wheeler, Megan; Newsome, Emily; Altman Klein, Helen
Abstract : Enhancing clinical expertise of novice nurses is a challenge for nursing professional development practitioners. Time and availability of expert preceptors are limited. This article describes a process evaluation project using a specific method of cognitive skills training to expose inexperienced nurses to expert thinking and help them develop more advanced cognitive skills. Development of scenarios, decision points, and expert rationale is described along with project outcomes and lessons learned. Nursing professional development practitioners and inexperienced nurses may benefit from using this method.